Evaluation of refuge technologies in transgenic maize crop - Zancanaro, Paolo Orlando; Buchweitz, Elizandra Döring; Boiça Junior, Arlindo Leal; Moro, José Roberto (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to compare the traditional refuges in separated areas with the alternative technology of refuge provided by the mixture ofÂ conventional seeds in the bag (refuge in the bag, RIB) with different proportions. The commercial transgenic hybrids AG 7000YG and DKB 390YG were used with the refuges sown with their respective conventional cultivars. Seven treatments were evaluated: RIB with four mixing rates of nontransgenic seeds (2.5, 5.0, 7.5, and 10%); traditional refuge, with 10% of the area sown exclusively with nontransgenic cultivar; and entirely cultivated areas with transgenic or nontransgenic plants. The DKB 390YG hybrid was the most productive. For this hybrid, there were no yield differences between treatments, except for the control (entirely conventional), which had lower yield. With the AG 7000YG, RIB technology with 5.0 and 7.5% of nontransgenic seeds provided the best yields, significantly higher than the one from traditional refuge, which did not differ from the conventional control. In the RIB treatments, differences in damage intensities by Spodoptera frugiperda did not reflect in yield differences. Refuge in the bag is a viable alternative to the currently used refuge method.